Monophasic-quadri-burst stimulation robustly activates bilateral swallowing motor cortices - Fujiki, Minoru; Hata, Nobuhiro; Anan, Mitsuhiro; Matsushita, Wataru; Kawasaki, Yukari; Fudaba, Hirotaka (Frontiers in Neuroscience, 2023)
A stable, reliable, non-invasive, quantitative assessment of swallowing function remains to be established. Transcranial magnetic stimulation (TMS) is commonly used to aid in the diagnosis of dysphagia. Most diagnostic applications involve single-pulse TMS and motor evoked potential (MEP) recordings, the use of which is not clinically suitable in patients with severe dysphagia given the large variability in MEPs measured from the muscles involved in swallowing. Previously, we developed a TMS device that can deliver quadripulse theta-burst stimulation in 16 monophasic magnetic pulses through a single coil, enabling the measurement of MEPs related to hand function. We applied a system for MEP conditioning that relies on a 5 ms interval-monophasic quadripulse magnetic stimulation (QPS5) paradigm to produce 5 ms interval-four sets of four burst trains; quadri-burst stimulation (QBS5), which is expected to induce long-term potentiation (LTP) in the stroke patient motor cortex. Our analysis indicated that QBS5 conditioned left motor cortex induced robust facilitation in the bilateral mylohyoid MEPs. Swallowing dysfunction scores after intracerebral hemorrhage were significantly correlated with QBS5 conditioned-MEP parameters, including resting motor threshold and amplitude. The degree of bilateral mylohyoid MEP facilitation after left side motor cortical QBS5 conditioning and the grade of severity of swallowing dysfunction exhibited a significant linear correlation (r = −0.48/−0.46 and 0.83/0.83; R2 = 0.23/0.21 and 0.68/0.68, P < 0.001; Rt./Lt. side MEP-RMT and amplitudes, respectively). The present results indicate that RMT and amplitude of bilateral mylohyoid-MEPs after left motor cortical QBS5 conditioning as surrogate quantitative biomarkers for swallowing dysfunction after ICH. Thus, the safety and limitations of QBS5 conditioned-MEPs in this population should be further explored.